The wave of remunicipalisation of energy networks and supply in Germany: the establishment of 72 new municipal power utilities - Oliver Wagner; Kurt Berlo (First fuel now: ECEEE 2015 Summer Study. Proceedings. 1-6 June 2015, Toulon/Hyères, France, 2015)
After a wave of privatizations in the end of the 1990s, the electrical power supply of many municipalities in Germany has been returned into public hands. Many municipalities discover chances and possibilities for local action, which arise with remunicipalisation. The local policy-makers realize that remunicipalisation offers the opportunity of implementing an independent energy policy at local level which is critical in creating a transformation to a sustainable energy system based on energy efficiency and renewable energies. The municipal ownership allows a strong governance towards more political influence in the local energy market. In addition, there is a clear opinion of the population: 81 % of citizens surveyed say they trust their local municipal utility, compared to only 26 % who say they trust corporations (VKU-Survey, 2010). In summary, there are many good reasons for local politicians to establish their own municipal utilities. The payback for municipalities is tangible when the local utility focuses on reliably providing affordable energy rather than on increasing its returns. The new municipal power utilities stimulate competition and contribute to the renewal / restructuring of the traditional energy market. The founding of 72 municipal utilities since 2005 leads us to ask for the reasons. The study reviews the German trend towards municipal ownership of local utilities, assessing their performance based on 10 targets related to the energy transition, climate protection, and the local economic impact: 1. Achieving environmental objectives and organization of the local "Energiewende". 2. Higher local added value. 3. Harnessing tax regulations for improving municipal services. 4. Improving the income situation of the city. 5. Democratization of supply and stronger orientation towards the common good (public value). 6. Creating and protecting good jobs. 7. Acting in social responsibility in energy supply. 8. Expansion of eco-efficient energy services. 9. Harnessing customer relations and public image. 10. Materialising synergies with other sectors. Based on expert opinions, the study finds out that the likelihood of these targets being reached is "high to very high". The aim of this article is to provide a compact and basic understanding of the possible reasons for the phenomenon of remunicipalisation.
urn:nbn:de:bsz:wup4-opus-59209
Keywords: 330